Nandrolone excretion in sedentary vs physically trained young women - Enea, C.; Boisseau, N.; Bayle, M. L.; Flament, M. M.; Grenier-Loustalot, M. F.; Denjean, A.; Diaz, V.; Dugue, B. (Scandinavian Journal of Medicine & Science in Sports, 2010)
We investigated the effects of the menstrual cycle, oral contraception and physical training on exhaustive exercise-induced changes in the excretion of nandrolone metabolites [19-norandrosterone (19-NA), and 19-noretiocholanolone (19-NE)] in young women. Twenty-eight women were allocated to an untrained group (n=16) or a trained group (n=12), depending on their physical training background. The untrained group was composed of nine oral contraceptive users (OC+) and seven eumenorrheic women (OC-), while the trained group was entirely composed of OC+ subjects. Three laboratory sessions were conducted in a randomized order: a prolonged exercise test, a short-term exercise test and a control session. Urine specimens were collected before and 30, 60 and 90 min after the exercise test and at the same times of the day during the control session. Urinary concentrations of nandrolone metabolites were determined by gas chromatography coupled to mass spectrometry. Urinary concentrations of 19-NA and 19-NE ranged from undetectable levels to 1.14 and 0.47 ng/mL, respectively. Nandrolone excretion was not affected by the menstrual cycle phase (early follicular vs mid-luteal), prior physical training, oral contraception or acute physical exercise. Therefore, a urinary concentration of 2 ng/mL of 19-NA appears to be fair as the upper acceptable limit in doping control tests for female athletes.